2009
DOI: 10.1371/journal.pone.0005545
|View full text |Cite|
|
Sign up to set email alerts
|

Dominant Negative Mutants of Bacillus thuringiensis Cry1Ab Toxin Function as Anti-Toxins: Demonstration of the Role of Oligomerization in Toxicity

Abstract: Background Bacillus thuringiensis Cry toxins, that are used worldwide in insect control, kill insects by a mechanism that depends on their ability to form oligomeric pores that insert into the insect-midgut cells. These toxins are being used worldwide in transgenic plants or spray to control insect pests in agriculture. However, a major concern has been the possible effects of these insecticidal proteins on non-target organisms mainly in ecosystems adjacent to agricultural fields.Methodology/Principal Findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
47
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 36 publications
5
47
0
Order By: Relevance
“…Also, it was reported that Cry1Ab mutants in helix ␣-4 were affected in pore formation activity and were inactive. The mutants in helix ␣-4 are dominant-negative inhibitors of Cry1Ab toxin (5,40).…”
Section: Discussionmentioning
confidence: 99%
“…Also, it was reported that Cry1Ab mutants in helix ␣-4 were affected in pore formation activity and were inactive. The mutants in helix ␣-4 are dominant-negative inhibitors of Cry1Ab toxin (5,40).…”
Section: Discussionmentioning
confidence: 99%
“…Dominant-negative inhibitors of VacA (15)(16)(17)(18)(19), protective antigen (20 -25), Cry1Ab (26), and ClyA (27) are believed to act through the formation of mixed oligomers containing both wild-type and mutant proteins. Direct evidence of mixed oligomers, based on Förster resonance energy transfer or co-immunoprecipitation, has been reported in a few studies (16,18,19,63).…”
Section: Discussionmentioning
confidence: 99%
“…Dominant-negative inhibitors are non-cytotoxic mutant forms of active toxins that are able to inhibit the activity of wild-type toxin when the two proteins are mixed together. Such dominant-negative inhibitors have been described for a diverse set of toxins, including Helicobacter pylori VacA (15)(16)(17)(18)(19), Bacillus anthracis anthrax toxin protective antigen (20 -25), Bacillus thuringiensis Cry1Ab (26), and Escherichia coli ClyA cytotoxin (27). Like VacA, protective antigen, Cry1Ab, and ClyA, the ⑀-toxin assembles into oligomeric complexes containing multiple toxin monomers (28 -30).…”
mentioning
confidence: 99%
“…of Cry1A toxins, supported that helices ␣-3, ␣-4, and ␣-5 are important for toxicity and pore formation, without affecting their binding interaction with toxin receptors (11)(12)(13)(14)(15). The helix ␣-3 participates in the oligomerization process (13), and it is proposed that the hydrophobic hairpin formed by helices ␣-4 and ␣-5 inserts into the phospholipid bilayer whereas the rest of amphipathic helices of domain I, excluding helix ␣-1, are spread on the membrane surface in an umbrella-like conformation (10, 16 -19).…”
mentioning
confidence: 95%